2019
DOI: 10.5530/ijpcs.2019.8.3
|View full text |Cite
|
Sign up to set email alerts
|

National Survey of the Pharmacokinetics Services at the Ministry of Health Hospitals in Saudi Arabia: Prescribing and Dispensing Medication

Abstract: Objectives: To explore the pharmacokinetics services at the Ministry of Health (MOH) hospitals in Saudi Arabia with an emphasis on prescribing and dispensing medication. Methods: This is a 2-month crosssectional national survey of pharmacokinetics services. The study consisted of two parts: the first part captures demographic information and the second part is a questionnaire with 43 questions divided into three domains. The questions are derived from the guidelines of the American Society of Health-System Pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In another survey, approximately 18% of community pharmacies reported to be performing clinical laboratory tests, including those for lithium and tricyclic anti-depressants TDM [ 31 , 32 ]. In Saudi Arabia, a recent survey demonstrated that, at 37.84% of hospitals, pharmacists have the ability to request an estimation of patients’ drug levels and, at 30.77% of hospitals, they have the ability to change drug sampling time [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another survey, approximately 18% of community pharmacies reported to be performing clinical laboratory tests, including those for lithium and tricyclic anti-depressants TDM [ 31 , 32 ]. In Saudi Arabia, a recent survey demonstrated that, at 37.84% of hospitals, pharmacists have the ability to request an estimation of patients’ drug levels and, at 30.77% of hospitals, they have the ability to change drug sampling time [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an Australian and New Zealand survey conducted in 2010 by Norris et al, the pharmacist was cited as being the most frequently accessed health professional to provide TDM in hospitals [ 21 ]. In a survey conducted in Saudi Arabia in 2018, pharmacists were able to request a drug level in 38% of hospitals [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have not discussed about the aspects of pharmacokinetics practice [20,21]. Most physicians requested for the analysis of drug levels such as aminoglycoside and vancomycin [12,21]. In comparison, the peak drug level is not necessarily of vancomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported on the impact of involvement of pharmacists in the therapeutic drug monitoring and pharmacokinetics services [7][8][9][10][11]. Other studies have investigated the pharmacokinetics survey services at various healthcare organizations [12][13][14][15][16][17][18][19]. However, to the best of our knowledge, there are only a few local studies conducted to assess the practice of pharmacokinetics services by physicians across Middle Eastern countries [20,21].…”
Section: Introductionmentioning
confidence: 99%